The Phenomenon of Islamophobia in Germany on Indonesian Online News Sites 2018-2023 - Azizah, Balkis Nur; Al Anshory, Abdul Muntaqim; Leesen, Adul (Fenomena, 2024)
Islamophobia does not only occur among non-Muslims but Islamophobia is also experienced by Muslims who do not agree with their thoughts. Islamophobia is a psychological symptom that sufferers experience when they encounter Muslims. The cause could be due to an unpleasant experience experienced by the sufferer, or because they are influenced by news reporting that Islam is a harsh religion, so that they feel afraid if they must face Muslims. The aims of this research are (1) to understand the picture of Islamophobia in Germany; (2) analyze the form of Islamophobia in Germany; and (3) describe the impact of Islamophobia in Germany. Researchers used descriptive qualitative methods with primary data sources in the form of online news and supported by related journals as secondary data. The results of the research are (1) Symptoms of Islamophobia in Germany have increased significantly every year; (2) the forms of Islamophobia found were the dissolution of mosques, harassment of Muslim women and prohibitions on wearing the headscarf, public opinion, work and education; (3) the impact of Islamophobia in Germany, namely psychological, social, legal and political policies. Islamophobia tidak hanya terjadi pada kalangan non-Muslim saja melainkan Islamophobia juga dialami oleh umat Islam yang tidak sependapat dengan pemikirannya. Islamophobia merupakan gejala psikis yang dialami penderita ketika mereka berhadapan dengan orang muslim. Penyebabnya bisa karena pengalaman yang tidak menyenangkan yang dialami oleh si penderita, ataupun karena terpengaruh oleh kabar yang memberitakan Islam sebagai agama yang keras, sehingga mereka merasa takut jika harus berhadapan dengan orang Islam. Tujuan dari penelitian ini adalah (1) mengetahui gambaran Islamophobia di Jerman; (2) menganalisis bentuk Islamophobia di Jerman; dan (3) menjabarkan dampak Islamophobia di Jerman. Peneliti menggunakan metode kualitatif deskritif dengan sumber data primer berupa berita online dan didukung dengan jurnal terkait sebagai data sekunder. Adapun hasil dari penelitian yakni (1) Gejala islamophobia di Jerman mengalami peningkatan yang signifikan di setiap tahunnya; (2) bentuk islamophobia yang ditemukan adalah adanya pembubaran masjid, terjadinya pelecehan perempuan muslimah dan larangan berjilbab, pendapat publik, pekerjaan dan pendidikan; (3) dampak dari Islamophobia di Jerman yakni dampak psikologis, sosial, kebijakan hukum dan politik.